Virtual stenting of intracranial aneurysms: A pilot study for the prediction of treatment success based on hemodynamic simulations. Issue 11 (November 2018) - Berg, Philipp; Saalfeld, Sylvia; Janiga, Gábor; Brina, Olivier; Cancelliere, Nicole M; Machi, Paolo; Pereira, Vitor M
Endovascular treatment of intracranial aneurysms using flow-diverting devices has revolutionized the treatment of large and complex lesions due to its minimally invasive nature and potential clinical outcomes. However, incomplete or delayed occlusion and persistent intracranial aneurysm growth are still an issue for up to one-third of the patients. We evaluated two patients with intracranial aneurysm located at the internal carotid artery who were treated with flow-diverting devices and had opposite outcomes. Both patients presented with similar aneurysms and were treated with the same device, but after a 1-year follow-up, one case presented with complete occlusion (Case 1) and the other required further treatment (Case 2). To reproduce the interventions, virtual stents were deployed and blood flow simulations were carried out using the respective patient-specific geometries. Afterward, hemodynamic metrics such as aneurysmal inflow reduction, wall shear stresses, oscillatory shear, and inflow concentration indices were quantified. The hemodynamic simulations reveal that for both cases, the neck inflow was clearly reduced due to the therapy (Case 1: 19%, Case 2: 35%). In addition, relevant hemodynamic parameters such as time-averaged wall shear stress (Case 1: 35.6%, Case 2: 57%) and oscillatory shear (Case 1: 33.1%, Case 2: 26.7%) were decreased considerably. However, although stronger relative reductions occurred in the unsuccessful case, the absolute flow values in the successful case were approximately halved. The findings demonstrate that a high relative effect of endovascular devices is not necessarily associated with the desired treatment outcome. Instead, it appears that a successful intracranial aneurysm therapy requires a certain patient-specific inflow threshold.